Stabilization Policies and Structural Reforms in Albania Since 1997 : Achievements And Remaining Challenges - Treichel, Volker (IMF Policy Discussion Papers; Policy Discussion Paper, 2002)
This paper assesses the effectiveness of stabilization policies and structural reforms in Albania since 1997 and seeks to identify the remaining key challenges in various policy areas. It also draws lessons for other transition economies from the recent Albanian experience. While progress has been made toward macroeconomic stability and the establishment of a modern institutional framework, much remains to be done to enhance the sustainability of the recent favorable macroeconomic performance and reduce unemployment and poverty. Crucial areas of reform are the creation of functioning institutions, notably in the judicial field, and the establishment of a reliable supply of electricity, which has recently become an obstacle for rapid growth.